Effectiveness of promotional tools and behavioral intention of tourist towards Melaka River Cruise (MRC) / Abd Hadi Zainudin - Zainudin, Abd Hadi (Faculty of Business and Management, 2010)
The main purpose of this study is to see how effectiveness of the promotional tools and behavioral intention of tourist towards the Melaka River Cruise (MRC). This research has been done in Melaka town area. The problem that face by the company in determining the effectiveness or the suitable promotional tools that can help them increase the Melaka River Cruise (MRC) customer come to get their service.